PhoU homologs from Staphylococcus aureus dimerization and protein interactions - Clayton T. Matthews; Sakib Mahmud; Stewart G. Gardner (Microbiology Spectrum)
ABSTRACT PhoU proteins are negative regulators of the phosphate response, regulate virulence, and contribute to antibiotic resistance. Staphylococcus aureus has multiple genes encoding PhoU homologs that regulate persister formation and potentially virulence, but the molecular mechanisms of this regulation are not fully understood. We used a bacterial adenylate cyclase two-hybrid system to assess interactions between PhoU homologs and other proteins known to interact with PhoU from Escherichia coli. S. aureus PhoU (also referred to as PhoU1) interacted with PhoU itself; PitR (also referred to as PhoU2) interacted with PitR itself. We identified potential structural and dimerization models for S. aureus PhoU homologs. Dimerization was confirmed using size exclusion chromatography of purified proteins. These results highlight the complex nature of PhoU proteins. Further analysis may elucidate the potential mechanisms for regulating gene expression, persister formation, and virulence in S. aureus.IMPORTANCEPhoU proteins affect pathogenesis and persister formation in many bacterial species. This protein is essential for signaling environmental phosphate levels in Escherichia coli but is still not well characterized in many other pathogenic bacterial strains. This work identifies some similarities and key differences in Staphylococcus aureus PhoU homologs compared to E. coli PhoU, specifically, PhoU and PitR from S. aureus form homodimers but do not appear to interact with PhoR or phosphate transporter proteins.